MODERN APPROACHES TO THE DEVELOPMENT OF PROFESSIONAL QUALITIES OF FUTURE TEACHERS OF PHYSICAL EDUCATION BASED ON NATIONAL VALUES - Kushmurodov Bekzod Abduraimovich (Bright Mind Publishing, 2025)
In the current context of globalization, the issue of harmonizing national values in education becomes especially relevant. The use of modern pedagogical and psychological approaches to the formation of professional qualities of future teachers in the field of physical education provides great opportunities. By combining the process of upbringing based on national values with modern innovative methods, not only the physical, but also the spiritual development of the younger generation is ensured.
Keywords: Modern training, interactive classes, information technology, national customs and traditions, physical, mental and spiritual development, independent thinking, creativity, initiative, national sports, folk games, national dances, traditional competitions.